Formation of Bezoar in an Elderly Patient with Alzheimer’s Disease: Bezoar in a Patient with Alzheimer - Casandra, G. R. (British Journal of Healthcare and Medical Research, 2022)
Bezoar is characterized as a mass that derives from a non-digestible foreign material and that accumulates in the gastrointestinal tract, usually in the stomach. This phenomenon usually occurs in people with some type of comorbidity or that have certain predisposing factors, such as gastrointestinal motility disorders or some psychiatric illness. There are different types of ingested materials that favor the formation of the bezoar and among the known materials we highlight the mattress foam, that generates an occupational bezoar. We report an unusual case of upper gastrointestinal bleeding due to gastric ulcers, resulting from an occupational bezoar in an elderly patient with Alzheimer’s disease, which was only discovered due to the symptoms of frequent vomiting and subsequently due to hematemesis and melena, due to gastric ulcers formed. The prevention of these incidents is a safe practice that must be performed by all professionals who deal with the elderly people with some type of vulnerability, especially those who has Alzheimer’s disease.